Pengaruh Efisiensi, Ketepatan, dan Keefektifan Kerja terhadap Penggunaan Microsoft Excel di Depok dan Bogor Rayy: The Effect of Efficiency, Accuracy, and Work Effectiveness on the Use of Microsoft Excel in Depok and Bogor - Rayyan Audria; Lovny Safira Ernisa; Lutfia Zahra; Sarah Putri Rachmani; Greace Jessica Valent Sihombing; Rudianto Rudianto (Jurnal Mnajemen | Ekonomi | Akuntansi, 2026)
Abstracts - Microsoft Excel is a number and data processing software automatically to create information data for decision making in research. This investigation aims to analyze the influence of efficiency, accuracy, and effectiveness in the world of work on the use of Microsoft Excel applications. The approach used is quantitative statistics with observation and survey methods through the distribution of questionnaires to the entire population of 180 respondents, using area sampling techniques (cluster sampling). Data were analyzed with the help of IBM SPSS version 26. The findings of the research show that efficiency has a positive and significant impact on the use of Microsoft Excel, with the results of the calculated t value of 2.565> t table 1.97353 and a significance value of 0.011 <0.05. Accuracy has a positive and significant impact on the use of Microsoft Excel, with the results of the calculated t value of 3.326> t table 1.97353 and a significance value of 0.001 <0.05. Effectiveness has a positive and significant effect on the use of Microsoft Excel, with a calculated t value of 3.758 > t table 1.97353 and a significance value of 0.000 < 0.05. Keywords: Efficiency, Accuracy, Effectiveness, Microsoft Excel